2013
DOI: 10.3109/09273948.2013.797472
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corneal Parameters with Scheimpflug Imaging in Patients with Rheumatoid Arthritis

Abstract: The results suggest that RA patients have thinner corneas compared to control subjects that may be affected by disease duration. Furthermore, coexistence of DE and RA seems to aggravate the thinning of cornea as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…8-10 However, a study using Pentacam rotating Scheimpflug camera has demonstrated that the cornea of patients with rheumatoid arthritis is thinner than that of normal populations, and the accompanying dry eye involves an additional significant decrement in corneal thickness in these patients. 7 Accordingly, Villani et al found that the corneas of patients with rheumatoid arthritis to be significantly thinner than those of control subjects in their in vivo confocal study. They found similar corneal thickness values in patients with rheumatoid arthritis with or without secondary Sjogren syndrome.…”
Section: Corneal Biomechanical Properties In Systemic Inflammatory DImentioning
confidence: 95%
See 4 more Smart Citations
“…8-10 However, a study using Pentacam rotating Scheimpflug camera has demonstrated that the cornea of patients with rheumatoid arthritis is thinner than that of normal populations, and the accompanying dry eye involves an additional significant decrement in corneal thickness in these patients. 7 Accordingly, Villani et al found that the corneas of patients with rheumatoid arthritis to be significantly thinner than those of control subjects in their in vivo confocal study. They found similar corneal thickness values in patients with rheumatoid arthritis with or without secondary Sjogren syndrome.…”
Section: Corneal Biomechanical Properties In Systemic Inflammatory DImentioning
confidence: 95%
“…6 The underlying mechanism of corneal thinning is believed to be due to chronic degradation of type IV collagen in the cornea by type IV collagenases produced by activated Langerhans cells. 7 Recently, a study also found a significant lower CCT in patients with another CVD-ankylosing spondylitis -when compared with aged-matched controls. 12 CCT in scleroderma has been subject to debate because of conflicting reports.…”
Section: Corneal Biomechanical Properties In Systemic Inflammatory DImentioning
confidence: 96%
See 3 more Smart Citations